Whose justice? Which rationality? - MacIntyre, Alasdair C. (University of Notre Dame Press, 1988)
Is there any cause or war worth risking one's life for? How can we determine which actions are vices and which virtues? MacIntyre, professor of philosophy at Vanderbilt University, unravels these and other such questions by linking the concept of justice to what he calls practical rationality. He rejects the grab-what-you-can, utilitarian yardstick adopted by moral relativists. Instead, he argues that four wholly different, incompatible ideas of justice put forth by Aristotle, Augustine, Aquinas and Hume have helped shape our modern individualistic world. In his unorthodox view, each person seeks the good through an ongoing dialogue with one of these traditions or within Jewish, non-Western or other historical traditions. This weighty sequel to After Virtue (1981) is certain to stir debate.